Implementasi Pembelajaran Berbasis Inkuiri dalam Upaya Meningkatkan Pemahaman Pelajaran PKn - Makmur Sembiring (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2019)
This research departs from the background of the need for renewal in improving the creativity of teaching teachers in the PKN learning process in junior high schools in response to increasing the shortcomings of students learning. In learning activities, both in the process and learning products can improve understanding. It is expected that the teacher is able to play the role of an innovator of learning, increasing the creativity of teachers better developed. In the context of increasing student learning outcomes and activities in PKN learning, CAR is conducted by using inquiry-based learning, the results of research show an increase in students' understanding of learning in class VII at Junior High School 1 Tigabinanga